2014
DOI: 10.3389/fmicb.2014.00549
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-derived biomarkers for active tuberculosis diagnosis

Abstract: Tuberculosis (TB) is an infectious disease caused by members of Mycobacterium tuberculosis complex. Despite the availability of effective treatments, TB remains a major public health concern in most low and middle-income countries, representing worldwide the second leading cause of death from an infectious disease. Inadequate case detection and failures to classify the disease status hamper proper TB control. The limitations of the conventional diagnostic methods have encouraged much research activities in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 52 publications
(57 reference statements)
0
35
0
Order By: Relevance
“…Accurate diagnosis and effective treatment is essential for TB control. Sputum bacteriological tests, such as mycobacterial culture and smear microscopy, are still the most commonly used diagnostic methods for TB 2. However, the sensitivity of these tests is limited, and obtaining results from mycobacterial culture takes several weeks 1 3.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate diagnosis and effective treatment is essential for TB control. Sputum bacteriological tests, such as mycobacterial culture and smear microscopy, are still the most commonly used diagnostic methods for TB 2. However, the sensitivity of these tests is limited, and obtaining results from mycobacterial culture takes several weeks 1 3.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the M. tuberculosis H37Rv CFP preparation provides a good representation of the secreted/shed proteins because many main proteins of MTB were identified, with minimal contamination of non-MTB proteins (only a few peptides of human keratin were detected). Proteins highly recognized by anti-CFP antibodies (HspX, EsxB and Secreted antigen 85-a FbpA (Rv3804c)) are relevant pathogen antigens [33,44], recognized as secreted proteins by others [8,13], and evaluated as pathogen-derived biomarkers for active tuberculosis diagnosis [9].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, considering the need of pathogen-derived biomarker validation for M. tuberculosis active diagnosis, we looked in the list of CFP for principal protein antigens detected in clinical samples [9], confirming the presence of 11 out of 12. Moreover, these putative biomarkers exhibited on average a high NSAF, being 10 of them in the P90% subgroup: GroEL2 (Rv0440), EsxA (Rv3875), HspX (Rv2031c), FbpA (Rv3804c), FbpB (Rv1886c), Mpt64 (Rv1980c), PstS1 (Rv0934), GlcB (Rv1837c), Apa (Rv1860) and FbpC (Rv0129c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations